Optimization of immunodot blot assay for diagnosis of Typhoid and Paratyphoid fever using the TPTest for comparison - Rahman, Nazia (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.